Awareness, attitude and barriers of colorectal cancer screening among high-risk populations in China: a cross-sectional study. Issue 7 (12th July 2021) - Huang, Ruo-lin; Liu, Qi; Wang, Ying-xin; Zou, Jin-yu; Hu, Li-feng; Wang, Wen; Huang, Ying-hui; Wang, Yi-zhuo; Zeng, Bo; Zeng, Xi; Zeng, Ying
Abstract : Objective: To assess the awareness, attitude and barriers of colorectal cancer screening among high-risk populations in China. Design: A cross-sectional study was employed. Setting: This study was conducted in nine hospitals in Hunan province, China. Participants: Individuals with a high-risk for colorectal cancer were interviewed using a pretested structured questionnaire. Primary and secondary outcome measures: Knowledge, attitude towards colorectal cancer screening, sociodemographic factors associated with screening knowledge and behaviour and barriers of colorectal cancer screening. Results: This study included 684 participants. The mean knowledge score was 11.86/24 (SD 4.84). But over 70% of them held a positive attitude towards screening. Only 13.3% had undergone colorectal cancer screening. Independent factors related to knowledge were education level of college or above, working as a white collar, higher income, having health insurance, having seen a doctor in the past year and with a high perceived risk (p<0.05). Factors independently associated with screening behaviour included personal history of colorectal disease, having seen a doctor in the past year, previous discussion of colorectal cancer screening, high perceived risk and better knowledge (p<0.05). Main reasons for not undergoing screening were no symptoms or discomfort (71.1%), never having thought of the disease or screening (67.4%) and no doctor advised me (29.8%). Conclusion: In China, the majority of high-risk people had deficient knowledge and had never undergone colorectal cancer screening. But most of them held a positive attitude towards the benefits of colorectal cancer screening. This has promising implications to design targeted educational campaigns and establish screening programmes to improve colorectal cancer awareness and screening participation. Healthcare professionals should advise high-risk individuals to participate in screening and inform them about cancer risk.